Ruthenium Nanoparticles in High‐Throughput Studies of Chemoselective Carbonyl Hydrogenation Reactions. Issue 3 (23rd December 2015) - Gmeiner, Julia; Behrens, Silke; Spliethoff, Bernd; Trapp, Oliver
Abstract: Small (≤1.4 nm) and very active Ru nanoparticles, stabilized in a polysiloxane matrix, were prepared and studied in hydrogenation reactions by the integration of catalysis and analysis. We used our strategy to combine catalytic activity and separation selectivity in a capillary microreactor, installed in a GC–MS instrument, to develop a fast and reliable screening tool for catalysis over Ru nanoparticles. A high conversion using a low catalyst loading of 0.3 mol % and temperature and long‐term stability of the catalytically active column were observed for the hydrogenation of various carbonyl compounds, which included aldehydes, ketones, and pyruvates. Additionally, we observed a high chemoselectivity for aromatic carbonyl systems. Comprehensive measurements were performed in this high‐throughput experimental setup to gain important insights into the kinetics of hydrogenation reactions at the interface between heterogeneous and homogeneous catalysis. Abstract : Nanoparticles for microreactors : Small (≤1.4 nm) and very active Ru nanoparticles, stabilized in a polysiloxane matrix, are prepared and studied in selective hydrogenation reactions by the integration of catalysis and analysis in a single step. A detailed kinetic analysis of the hydrogenation of carbonyl compounds is presented.